2014
DOI: 10.4028/www.scientific.net/amm.695.380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination Factors of Operating Pressure, Nozzle Diameter and Riser Height on Sprinkler Irrigation Uniformity

Abstract: The irrigation uniformity of sprinkler irrigation system depends on many design factors such as nozzle type, nozzle diameter, operating pressure and riser height. An experimental study was performed to investigate the effect of combination factors of operating pressure, nozzle diameter and riser height on sprinkler irrigation uniformity. Different operating pressures, nozzle diameters and riser heights have been used. The irrigation uniformity coefficients such as coefficient of uniformity (CU) and distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
2
4
0
1
Order By: Relevance
“…These findings were in good agreement with the results reported by Hui et al (2021a), who found that although the nozzle diameter had a certain effect on the maximum shear stress, the overall effect was insignificant. In addition to droplet shear stress, kinetic energy and specific power of low-pressure sprinkler were also found to be insignificantly affected (P>0.05) by operating pressure and nozzle diameter (Hui et al, 2022b), but this result was not supported by Bautista-Capetillo et al ( 2012) on a VYR35 sprinkler and Osman et al (2015) on a double nozzle impact sprinkler. One possible explanation is that their studies were conducted based on medium-and high-pressure sprinklers such as impact sprinklers.…”
Section: Effect Of Various Factors On the Distribution Of Droplet She...mentioning
confidence: 78%
“…These findings were in good agreement with the results reported by Hui et al (2021a), who found that although the nozzle diameter had a certain effect on the maximum shear stress, the overall effect was insignificant. In addition to droplet shear stress, kinetic energy and specific power of low-pressure sprinkler were also found to be insignificantly affected (P>0.05) by operating pressure and nozzle diameter (Hui et al, 2022b), but this result was not supported by Bautista-Capetillo et al ( 2012) on a VYR35 sprinkler and Osman et al (2015) on a double nozzle impact sprinkler. One possible explanation is that their studies were conducted based on medium-and high-pressure sprinklers such as impact sprinklers.…”
Section: Effect Of Various Factors On the Distribution Of Droplet She...mentioning
confidence: 78%
“…Many studies have informed that the heterogeneity in water distribution has a negative impacts on the efficiency of water management 1 . Furthermore, the pressurized irrigation systems such as drip and sprinkler irrigation have become more efficient and feasible to apply to increase the water use efficiency 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Keller and Bliesner (1990) (Tarjuelo et al, 1999a). Low values of CU indicate incorrect combination of nozzle size, operating pressure, and other design factors (Salmerón et al, 2012;Siosemarde et al, 2012;Osman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%